Pembuatan Telur Asin Sebagai Bekal Kewirausahaan Pada Siswa Madrasah Aliyah NW Praida Kroya - Muhammad Sanusi Sanusi; Titik Husnawati Amini; Muhamad Akrom; Zihab Zihab; Muh Ariadi Muslin (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2024)
The aim of this activity is to improve the skills of Class X, XI, and XII students of Madrasah Aliyah NW Praida Kroya. The method is done by providing training and guidance on making various salted eggs. The activity was carried out on April 1, 2024 at Madrasah Aliyah NW Praida Kroya with 33 students participating. The results of the activity showed that participants were able to make salted eggs according to the planned program. The conclusions obtained from this activity are that it can increase knowledge for students of Madrasah Aliyah NW Praida Kroya class about various processed salted eggs that can be made and crafted by themselves. In addition, it can increase knowledge of how to make good salted eggs, and also increase the confidence of training Participants